2021
DOI: 10.33003/fjs-2021-0501-609
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal and Extra-Gonadal Sperm Reserves of Kano Brown Bucks as Influenced by Season and Feeding Regime in Semi-Arid Zone of Nigeria

Abstract: The study was conducted to evaluate the effect of season and feeding regime on reproductive parameters of Kano Brown bucks. A total of fourty eight (48) bucks were used for this study which comprised sixteen (16) bucks per season. At the end of this study twelve (12) bucks, three from each treatment were orchidectomised. Twenty-four right and left testes were harvested, testicular weight (g) and length (cm) were measured. Epididymis was carefully separated from the testes using scapel blade and then separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
1
1
Order By: Relevance
“…The EE obtained from this study fell within the range of 22.10 g kg -1 DM -42.21g kg -1 DM reported by Njidda et al (2018). The Lignin content reported from this study is higher than that reported by Nasir et al (2014) and Njidda et al (2016). Differences observed in the composition of the feed are attributed to the ration used as Njidda et al (2018) used a mix of soybean meal and Gmelina arborea leaves, Nasir et al (2014) used cotton seed cake while a mixed ration of cowpea husk and tiger nut residue was used for this study.…”
Section: Chemical Composition Of Experimental Dietscontrasting
confidence: 78%
See 1 more Smart Citation
“…The EE obtained from this study fell within the range of 22.10 g kg -1 DM -42.21g kg -1 DM reported by Njidda et al (2018). The Lignin content reported from this study is higher than that reported by Nasir et al (2014) and Njidda et al (2016). Differences observed in the composition of the feed are attributed to the ration used as Njidda et al (2018) used a mix of soybean meal and Gmelina arborea leaves, Nasir et al (2014) used cotton seed cake while a mixed ration of cowpea husk and tiger nut residue was used for this study.…”
Section: Chemical Composition Of Experimental Dietscontrasting
confidence: 78%
“…The crude protein content decreased as the level of cowpea husks decreased with increasing levels of Tiger nut residue. The crude protein level in this study is within the range of 139 g kg -1 DM to 220 g kg -1 DM reported by Olafadehan et al (2022) who used cowpea husks to feed goats but lower than the range of 162.1 -203.3 g kg-1 DM and 354 g kg -1 DM to 383 g kg -1 DM reported by Njidda et al (2018) and Nasir et al (2014) respectively. Abdu et al (2012) and Okafor et al (2012) reported 102.5 and 137.3 g kg -1 DM which is lower than the results from this study.…”
Section: Chemical Composition Of Experimental Dietssupporting
confidence: 63%
“…The crude protein level in this study fell within the range of 139 g kg -1 DM to 220 g kg -1 DM reported by Olafadehan et al (2022) who used cowpea husks to feed goats but lower than the range of 162.1-203.3 g kg -1 DM and 354 g kg -1 DM to 383 g kg -1 DM reported by Njidda et al (2018) and Nasir et al (2014) respectively. Abdu et al (2012) and Okafor et al (2012) reported 102.5 and 137.3 g kg -1 DM which is lower than that obtained from this study.…”
Section: Chemical Composition Of Experimental Dietssupporting
confidence: 66%
“…The EE obtained from this study fell within the range of 22.10 g kg -1 DM -42.21g kg -1 DM reported by Njidda et al (2018). The Lignin content reported from this study is higher than that reported by Njidda et al (2018) and Nasir et al (2014). Differences observed in the composition of the feed are attributed to the ration used as Njidda et al (2018) used a mix of soyabean meal and Gmelina arborea leaves, Nasir et al (2014) used cotton seed cake while a mixed ration of cowpea husk and tiger nuts residue was used for this study.…”
Section: Chemical Composition Of Experimental Dietsmentioning
confidence: 48%